Analisis Pengangguran Usia Muda di Pulau Jawa Sebelum dan Saat Pandemi Covid-19 - Meilani Thereza Br. Saragih; Hardius Usman (Jurnal Studi Pemuda, 2021)
The Covid-19 pandemic has harmed the employment sector. Many companies do layoffs of employees and limit the recruitment of new employees. As a result, there is an increase in unemployment, especially in the younger age group. This study aims to analyze the status of youth unemployment in Java in the period before and during the Covid-19 pandemic, as well as the effect of the Covid-19 pandemic on youth unemployment in Java. The island of Java was chosen as the research locus because it is the area most affected by the Covid-19 pandemic in Indonesia. To achieve these objectives, we used the binary logistic regression analysis method with interaction effect. The results showed that gender, residency, education level, graduation time, marital status, work experience, and migration status affected the youth unemployment status in Java before and during the Covid-19 pandemic. In addition, the occurrence of the Covid-19 pandemic in 2020 affected youth unemployment in Java Island. There are different conditions of youth unemployment status in the period before and during the Covid-19 pandemic in terms of residency, education level, work experience, and migration status.